Dual-Parameter Fiber Sensors for Salinity and Temperature Measurement Based on a Tapered PMF Incorporated With an FBG in Sagnac Loop - Yuhui Liu; Weihao Lin; Fang Zhao; Xuming Zhang; Li-Yang Shao (IEEE Photonics Journal, 2024)
A flexible and stable optical fiber sensor based on the Sagnac loop is proposed and experimentally demonstrated for the measurement of salinity and temperature, simultaneously. The sensing unit consists of a tapered polarization maintaining fiber (tPMF) and a fiber Bragg grating (FBG) connected in series in the Sagnac loop. The temperature response comes from the high birefringence of PMF inside Sagnac loop, and the salinity response is enabled by the high-order modes excited in the tapered area of PMF. Besides, the FBG is for temperature compensation. We have succeeded in implementing dual-parameter measurements with the sensitivities of 0.356 nm/‰ for salinity and 0.616 nm/°C for temperature, respectively. The designed sensor has the potential for long-term monitoring of real ocean states.